Molar Uprighting Using Mini-Screws after Distalization by the Pendulum Appliance: A Case Report - Amir Moradi; Behrad Tanbakuchi; Hooman Shafaee (Mashhad University of Medical Sciences, 2013)
A 16-year-old Class II female patient was treated without tooth extraction. The upper first molars were distalized by the Pendulum appliance. After six months, the molars tipped significantly to the distal. To correct this side effect, we decided to upright the molars using skeletal anchorage. On each side, a mini-screw was inserted between first and second premolars in the buccal cortical plate. An auxiliary spring was placed between the mini-screw head and the molar buccal tube. The resultant moment made the first molar upright. In addition, the side effects of this mechanic, i.e. molar intrusion and molar buccal tipping, counteract the extrusion and medial movement caused by the Pendulum Appliance. The aim of this case report was to present an innovative method for molar uprighting using skeletal anchorage.